2009
DOI: 10.1159/000212101
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Mesenchymal Tumor of the Breast: Primary Chondrosarcoma

Abstract: Background: Primary mesenchymal tumors are an extremely rare malignancy of the breast. Case Report: A 52-year-old woman presented with a rapidly growing breast mass. Physical examination established a large and round mass with regular margins in the upper-outer quadrant of the right breast. Ultrasound showed a hypoechoic solid mass (41 ×36 mm) with lobulated contours. Mammography revealed a hyperdense and relatively regular-shaped mass giving the impression of a benign tumor. However, a pathologic report of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…They have been reported to develop from existing cystosarcoma phyllodes, fibroadenoma and cystic backgrounds [11]. Carcinosarcoma is characterized by the loss of intercellular adhesion, down-regulation of epithelial makers (cytokeratins), upregulation of mesenchymal markers [Vimentin and smooth muscle actin (SMA)], increase in motility, invasiveness, and metastatic capabilities [12][13]. In the present case, immunohistochemical staining showed the epithelial component to be positive for cytokeratin, while sarcomatous cells were positive for smooth muscle actin, and both components were positive for Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported to develop from existing cystosarcoma phyllodes, fibroadenoma and cystic backgrounds [11]. Carcinosarcoma is characterized by the loss of intercellular adhesion, down-regulation of epithelial makers (cytokeratins), upregulation of mesenchymal markers [Vimentin and smooth muscle actin (SMA)], increase in motility, invasiveness, and metastatic capabilities [12][13]. In the present case, immunohistochemical staining showed the epithelial component to be positive for cytokeratin, while sarcomatous cells were positive for smooth muscle actin, and both components were positive for Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection remains the only curative treatment option 13 and adjuvant therapy was therefore not a valid option. The patient agreed with our decision and has remained disease free for 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant treatment can decrease the rates of local and systematic recurrences, but the results are not significant because of the rarity of this pathological entity and the small number of cases reported, which makes the evaluation of the role of chemotherapy and radiotherapy in primary breast chondrosarcoma more difficult [7,9,10]. In Emad et al .’s study of malignant matrix-producing breast tumors (MP-MBC), they concluded that most MP-MBCs are variants of metaplastic breast carcinoma (MBC) with predominant mesenchymal components behaving similarly to ductal carcinomas.…”
Section: Discussionmentioning
confidence: 99%